Intrafirm trade with ASEAN countries by Japanese and US multinational corporations - Martin Groß (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1986)
During the last decade, the role of multinational corporations in international trade has received a steadily increasing attention. In a wide sense, multinational corporations are reported to manage an increasing share of international trade thereby bridging the gap between production for local and foreign markets and intensifying the international division of labour. In a narrow sense, trade between parent companies and their overseas affiliates (so called intrafirm trade) has provoked attention because this trade may challenge - by its very nature - conventional understanding of determinants of international trade and the impact of trade policies. The evidence on intrafirm trade is scant at best, however, and is almost exclusively related to the US. Therefore this paper tries to update and improve the empirical basis on intrafirm trade by giving answers to the following questions: - Which role does intrafirm trade play in international trade of home-countries other than the US? - Is intrafirm trade of major home countries region-specific and/or industry-specific and if so what are the specific characteristics of regions and industries where intrafirm trade is relatively important? - How has intrafirm trade developed over time? - Does the structural pattern of intrafirm trade conform to that of the underlying activity, that is foreign direct investment?
Keywords: 330; Multinationales Unternehmen; ASEAN-Staaten; Japan; USA